Solvent‐Adaptive Behavior of Oligospirobifluorenes at the Surface of Quartz Crystal Microbalances—A Conformational Process. Issue 8 (19th January 2017) - Pyka, Isabella; Lubczyk, Daniel; Saiju, Mandira D. S.; Salbeck, Josef; Waldvogel, Siegfried R.
Abstract: Oligospirobifluorenes represent promising building blocks for the generation of microporous sensor materials based on their restricted flexibility. The contact with specific solvents leads to a change of the three‐dimensional spirobifluorene structure. The single fluorene moieties unfold to an open structure with an increased volume due to intermolecular interactions with the solvent, detectable by NMR spectroscopy. The induced microporosity was further investigated by affinity comparisons of aromatic analytes with high fundamental frequency quartz crystal microbalances. Abstract : Flexibility determines properties : Oligospirobifluorene derivatives display a unique behavior towards solvent vapors. When the host material is conformationally flexible, it may convert into an open structure upon solvation (see figure). This reversible process takes place within minutes and can be observed by gravimetric methods as well as in solution using 1 H DOSY experiments.